Control over the morphology and phase of MnOx formed in the modified Hummers' method and impact on the electrocapacitive properties of MnOx–graphite oxide composite electrodes. Issue 50 (6th May 2016) - Sun, Xiaoming; Liu, Peng; Gu, Yi; Rufford, Thomas E.; Zhao, X. S.
Abstract : The controllable morphology and crystalline phase of manganese oxides formed in the Hummer's method have an impact on the electrocapacitive performance of the resulting composite materials. Abstract : We report an one-pot method to prepare manganese oxide decorated graphite oxide as composite electrode materials for supercapacitors. Dispersed manganese oxide particles were precipitated on the graphite oxide surfaces from KMnO4 added during the synthesis of graphite oxide by using a modified Hummers' method. The morphology and crystalline phase of the manganese oxide can be controlled by adjusting the mass ratio of KMnO4 /graphite. The sample prepared with a KMnO4 /graphite mass ratio of 2 contained nanoflowers of MnO2 phase and exhibited a specific capacitance of 120 F g −1 in 6 M KOH at a current density of 0.2 A g −1 . This composite retained 85% of its original capacitance after 2000 cycles, indicating an excellent stability against cycling.